Synthesis, cytotoxic activity and DNA interaction of Pd(II) complexes bearing N′-methyl-3,5-dimethyl-1-thiocarbamoylpyrazole - Barra, Carolina V. [UNESP]; Rocha, Fillipe V. [UNESP]; Gautier, Arnaud; Morel, Laurent; Quilles, Marcela B. [UNESP]; Carlos, Iracilda Z. [UNESP]; Treu-Filho, Oswaldo [UNESP]; Frem, Regina C.G. [UNESP]; Mauro, Antonio Eduardo [UNESP]; Netto, Adelino V.G. [UNESP] (Elsevier, 2013)
A new series of complexes of general formulae [PdX2(tmdmPz)] {X = Cl (1), Br (2), I (3), SCN (4); tmdmPz = N′-methyl-3,5-dimethyl-1- thiocarbamoylpyrazole} have been synthesized and characterized by elemental analysis, molar conductivities, IR, 1H and 13C{ 1H} NMR spectroscopy. In these complexes, the tmdmPz coordinates to Pd(II) center as a neutral N,S-chelating ligand. The geometries of the complexes have been optimized with the DFT method. Cytotoxicity evaluation against LM3 (mammary adenocarcinoma) and LP07 (lung adenocarcinoma) cell lines indicated that complexes 1-4 were more active than cisplatin. The binding of the complexes with a purine base (guanosine) was investigated by 1H NMR and mass spectrometry, showing that the coordination of guanosine occurs through N7. Electrophoretic DNA migration studies showed that all of them modify the DNA tertiary structure. © 2013 Elsevier Ltd. All rights reserved.
Keywords: Cytotoxicity; DNA binding; N′-methyl-3,5-dimethyl-1-thiocarbamoylpyrazole; Palladium(II); Spectroscopy